Frequency of Pregnancy Induced Hypertension (PIH) in Patients Presenting with Hypothyroidism - Naveeda Atif, Javaria Imran, Erum Ilyas, Saira Jamsheed, Zakia Shakeel, Adnan Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Preeclampsia is a potentially fatal condition during pregnancy and following delivery. Numerous organs' functions can be influenced by preeclampsia. It is crucial, as this illness may be linked to abnormalities in thyroid function. Therefore, the aim of this study was to assess the frequency of thyroid dysfunction and its association with hypertension in pregnant women. Methodology: This descriptive cross sectional study was conducted at Obstetrics and Gynecology Unit-I, Civil Hospital, Karachi, using a non-probability consecutive sampling technique. The duration of the study was about six months from October 2022 till March 2023. A total of 80 pregnant women who were between the ages of 18 and 40, had gestational ages between 20 and 40 weeks, and had laboratory results that suggested hypothyroidism were included in this study. A chi-square test was applied to evaluate the association between maternal age, parity, gestational age, serum levels of TSH and T4 and pregnancy induced hypertension. Results: The study findings showed that most of the women 33(41.25%) were between 26 to 35 years of age. The mean age of the pregnant women was 29.43±4.64 years. The mean parity was 1.74±0.83 and the mean gestational age was 30.33±5.22 weeks, and the mean duration of hypothyroidism was 4.27±2.06 years. Concerning thyroid parameters, the mean T4 was 5.79±1.21 pmol/L, and the mean TSH was 6.28±2.03 mIU/L. Additionally, there was an insignificant association observed between pregnancy induced hypertension and maternal age, gestational age, parity, and thyroid hormone parameters. Conclusion: This study concluded that alterations in the thyroid function of pregnant women led to pregnancy induced hypertension. Only 25% of hypothyroid pregnant women had gestational hypertension. Furthermore, age, parity, gestational age, and thyroid parameters of pregnant women were insignificantly associated with pregnancy induced hypertension. Keywords: Pregnancy induced hypertension, hypothyroidism, gestational age.